Diagnostic Usefulness of 3 Tesla MRI of the Brain for Cushing Disease in a Child - Ono, Erina (The Japanese Society for Pediatric Endocrinology, 2011)
It is sometimes difficult to confirm the location of a microadenoma in Cushing disease. Recently, we experienced an 11-yr-old female case of Cushing disease with hyperprolactinemia. She was referred to our hospital because of decrease of height velocity with body weight gain. On admission, she had typical symptoms of Cushing syndrome. Although no pituitary microadenomas were detected on 1.5 Tesla MRI of the brain, endocrinological examinations including IPS and CS sampling were consistent with Cushing disease with hyperprolactinemia. Oral administration of methyrapone instead of neurosurgery was started after discharge, but subsequent 3 Tesla MRI of the brain clearly demonstrated a 3-mm less-enhanced lesion in the left side of the pituitary gland. Finally, transsphenoidal surgery was performed, and a 3.5-mm left-sided microadenoma was resected. Compared with 1.5 Tesla MRI, 3 Tesla MRI offers the advantage of a higher signal to noise ratio (SNR), which provides higher resolution and proper image quality. Therefore, 3 Tesla MRI is a very useful tool to localize microadenomas in Cushing disease in children as well as in adults. It will be the first choice of radiological examinations in suspected cases of Cushing disease.